Do norms travel? The case of gender in Danish development cooperation. (July 2018) - Engberg-Pedersen, Lars
Questioning diffusion and translation as central concepts describing how norms influence policies, the article analyses the drafting process of a recent gender equality policy in Danish development cooperation. Three global norms (gender mainstreaming, sexual and reproductive health and rights, and women's empowerment) and their influence on the policy are examined, and it is argued that the contingency of policymaking circumscribes the role of global norms. A variety of intra- and extra-organizational factors affect the drafting of the policy, and it is the interaction between these factors and the norms, rather than diffusion or translation of global norms, that best describes the normative influence on Danish gender equality policy.